Public-Private Partnerships With Unhealthy Commodity Industries: Are They Undermining Real Progress in NonCommunicable Disease Prevention?; Comment on "Competing Frames in Global Health Governance: An Analysis of Stakeholder Influence on the Political Declaration on Non-communicable Diseases" - Chiara Rinaldi (Kerman University of Medical Sciences, 2022)
Public-private partnerships (PPPs) and whole-of-society approaches are increasingly common in public health promotion and non-communicable disease prevention, despite a lack of evidence in favour of their effectiveness in improving health outcomes. While PPPs may have advantages, they also give industry actors more influence over the design and implementation of public health strategies and interventions. Partnering with unhealthy commodity industries in particular - including the alcohol and ultra-processed food and beverages industries - can pose significant risks to public health due to these industries' deep-rooted conflicts of interest. In this commentary, I reiterate Suzuki et al.'s message about the importance of assessing and managing conflicts of interest before engaging with non-state actors through PPPs or other forms of engagement.